Weather prediction with machine learning - Liew, Hon Weng (Nanyang Technological University, 2023)
The world is made up of countless uncertainties and many of which cause irreversible damage to human life. The weather is one of the most unpredictable things in nature, and it affects our day-to-day lives on a scale many would never have thought of ordinarily. From minor inconveniences like getting drenched in the rain, to vital processes to human growth through agricultural means, accurate weather prediction is paramount to the quality of life.